2017
DOI: 10.1002/cepa.78
|View full text |Cite
|
Sign up to set email alerts
|

01.30: Evaluation on clamping load of high strength bolts under ambient environment

Abstract: The torque shear type high strength bolt is clamped in general when pin-tail of shank is cut off. However the clamping loads of high strength bolt did not often meet the required tension due to variation of torque coefficient. This is why the viscosity of lubricant on bolt shank affects the torque coefficient by temperature, dust and debris. In this study, the clamping tests of various high strength bolts were performed independently both at indoor condition and at construction sites for six years. The tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It could be shown that the required tightening torque which is needed to achieve a specific preload level decreases with increasing temperature and that the required preload is achieved with increasing system reserves for a pre-specified tightening torque. Furthermore, investigations regarding temperature influences on the preload of TCBs were carried out by field and laboratory tests [21]. Herein, laboratory test data and data from 24 construction sites were collected over a quality inspection time of five years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It could be shown that the required tightening torque which is needed to achieve a specific preload level decreases with increasing temperature and that the required preload is achieved with increasing system reserves for a pre-specified tightening torque. Furthermore, investigations regarding temperature influences on the preload of TCBs were carried out by field and laboratory tests [21]. Herein, laboratory test data and data from 24 construction sites were collected over a quality inspection time of five years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Izumi and Yokoyama et al [21,22] analyzed relaxation of screw joints with spring washers using the finite element method. In [23][24][25][26][27][28][29][30][31][32], loosening of screws of different types, geometry, and materials, was investigated by considering various clamping forces and temperatures: relaxation rate was related to clamping force. Friction between joint parts were investigated in [31,32] and 2 of 16 connection reliability was related to friction.…”
Section: Introductionmentioning
confidence: 99%